Multiple dimensions of regional variation of impoverishment in Iran - Hosnieh Mahoozi (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2015)
Concerning the demands of Sen's (1987) Capabilities Approach to assessment of human wellbeing, the paper estimates the values of frequency and breadth of multidimensional poverty in Iran. It distinguishes specific regions as Tehran, other urban areas, and rural areas and it reveals that the proportion of rural areas in multidimensional poverty has increased from 1999 to 2007, in spite of relatively high rate of GDP growth in that period. It also detects the specific socio-economic group's deprivation type which is invaluable information for effective policy targeting.
Keywords: D63; O53; 330; multi-dimensional poverty; welfare distribution; Iran